Group Counseling as a Mediator of the Relationship Between Academic Stress Levels and School Well Being - Damayanti, Esti; Erwan Syah, Muhammad (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Students' problems in dealing with the pandemi era resulted in a low level of school well being which would have an impact on academic stress levels. This is what drives researchers to conduct research related to group counseling as a mediator of the relationship between academic stress levels and school well-being in the subject of Islamic Religious Education at SMP Muhammadiyah Al Mujahidin Gunung Kidul. This research is a quantitative research with a correlational approach (looking at the relationship between variables). The data collection method used to obtain data from the three variables (Academic Stress Level, School well being and Group Counseling). The subjects of this study were 90 students of class VII in the subject of Islamic Religious Education at SMP Muhammadiyah Al Mujahidin Gunung Kidul. The subjects in the study were women and men. The results of this study are that hypothesis 1 is accepted, that is, there is a relationship between academic stress levels and school well being in Islamic Religious Education subjects at SMP Muhammadiyah Al Mujahidin Gunung Kidul. The data analysis technique used in this study is multiple linear regression analysis.Permasalahan siswa dalam menghadapi masa era pandemi tersebut membuat rendah tingkat school well being yang akan berdampak pada tingkat stres akademik. Hal inilah yang mendorong peneliti dalam melakukan penelitian terkait konseling kelompok sebagai mediator hubungan antara tingkat stres akademik dengan school well-being pada mata pelajaran Pendidikan Agama Islam di SMP Muhammadiyah Al Mujahidin Gunung Kidul. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan korelasional (melihat hubungan antar variabel). Metode pengumpulan data yang digunakan untuk memperoleh data dari ketiga variabel (Tingkat Stres Akademik, School well being dan Konseling Kelompok). Subjek penelitian ini adalah 90 siswa kelas VII pada mata pelajaran Pendidikan Agama Islam di SMP Muhammadiyah Al Mujahidin Gunung Kidul. Subjek dalam penelitian yaitu perempuan dan laki-laki. Hasil penelitian ini adalah bahwa hipotesis 1 diterima yaitu ada hubungan antara tingkat stres akademik dengan school well being pada mata pelajaran Pendidikan Agama Islam di SMP Muhammadiyah Al Mujahidin Gunung Kidul. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis regresi linear berganda.